First report of a urinary Pseudomonas juntendi carrying blaNDM-1 and blaIMP-15 co-integrated into the chromosome via ICE-IS91 and integron-Tn402-like transposition modules - Wang, Ziheng; Li, Jie; Li, Yingying; Chen, Zihao; Ren, Enze; Zhang, Peng (Frontiers in Microbiology, 2026)
BackgroundPseudomonas juntendi is an emerging opportunistic pathogen first described in 2019, whose antimicrobial resistance mechanisms and clinical significance remain poorly understood. In this study, we report the first urinary isolate of P. juntendi (PJ1) co-harboring blaNDM-1 and blaIMP-15, and comprehensively analyzed its phylogeny, resistance architecture, and biological characteristics.MethodsSpecies identification and phylogenetic placement were determined using whole-genome sequencing and average nucleotide identity analyses. Genomic annotation was applied to resolve the structure of resistance islands. Biofilm formation, stress tolerance, and virulence were assessed through crystal violet staining, environmental stress assays, and Galleria mellonella infection models, respectively.ResultsPhylogenomic analysis revealed that PJ1 clustered with isolates from China and Japan, forming an East Asian lineage suggestive of regional dissemination. Genomic analysis showed that PJ1 carries two metallo-β-lactamase modules integrated into the chromosome: blaNDM-1 embedded within an ICE–IS91 composite island and blaIMP-15 located in an integron-Tn402-like module, representing a mosaic multidrug resistance island. Phenotypically, PJ1 exhibited robust biofilm formation, tolerance to bile salts and hyperosmotic stress, and high virulence in the G. mellonella model.ConclusionPJ1 represents the first urinary P. juntendi isolate carrying both blaNDM-1 and blaIMP-15 on a single chromosome. Its composite resistance island and strong colonization capacity suggest that P. juntendi may serve as an emerging reservoir for metallo-β-lactamase dissemination, posing potential clinical and epidemiological threats.